Ageing Care Centre Women Entrepreneur: A Silver Bullet for Ageing Tsunami in Malaysia (Sains Humanika, 2019)
An ageing population is a global problem, and it affects all aspects of life. Globally, a drastic increase in the elderly population has been recorded, which is almost three times from the year 1980 (259 million) to 2025 (761 million). Similar trend also takes place in Malaysia, even though Malaysia is categorized as a developing country. Its population census reported an intense increase in ageing population from the year 2005 (7%), which is expected to be double (14%) by the year 2028. In addition, women comprise about half of the population in Malaysia. Thus, the Malaysian Government has acknowledged the importance of women entrepreneurs in the country’s economic growth. The report estimates that 20% of the entire registered business in Malaysia run by women, and about 650,000 women are engaged in various business activities. Currently, there are about 365 ageing care centres in Malaysia, and women entrepreneurs run a few of them, as sole ownership or partnership. The Malaysian Government is gradually facing the worrisome situation of dealing with the ageing population, as until the year 2030, Malaysia will be in the line of ageing group countries. Due to ageing population importance, this study inquires the situation of Malaysian women as ageing care centre entrepreneur, and ageing population issues in Malaysia. To gather the information, the qualitative research strategy, and semi-structured interviews technique was chosen for data collection. The target population of this study are five women entrepreneurs of ageing care centres in Malaysia. The findings highlight the social problems of elderly and difficulties of Malaysian women entrepreneur in care centre business such as funding, licensing issues, less technology, staff retention, and lack of trained staff. The results show that successful entry of womenfolk in ageing care centres business will bring significant social change and will help the government to overcome the challenge of the ageing population. This study will help the policymakers to formulate strategies for women entrepreneurship in Malaysia, especially the care centres entrepreneurs. Hence, the women can act as a silver bullet to subside the ageing tsunami that will crash Malaysians’ social life comfort.
Keywords: Ageing population; women; entrepreneur; business; care centres; elderly